Description of Body Mass Index in Tuberculosis Patient with Anti Tuberculosis Drugs Therapy in Unit Pengobatan Penyakit Paru Paru (UP4) Pontianak - ., Edo Putra Priyantomo (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Tuberculosis is an infectious disease with a chronicinflammation caused by Mycobacterium tuberculosis. This disease affectsnutritional status to its patient through its chronic inflammation, causingsome serious malnutrition in most of the patients. Tuberculosis needs aspecial treatment with special drugs called Anti Tuberculosis Drugs in along period. These drugs can also worsen the nutritional status oftuberculosis patient through its side effects. Objective. This research wasmade to measure Body Mass Index (BMI) of TB patients at the beginningof therapy, after 2 months, and after 6 months of TB therapy. Method.Case records of active TB with first line therapy of ATD treated betweenDecember 2009 until December 2013 at UP4 Pontianak.Â  Data was takenseparately between body weight, which is taken from case record, andbody height , which is taken from the patient due to the missing record inUP4, to measure the BMI after diagnosed, after 2 months, and after 6months of TB therapy. Result. Most of subject of this research areunderweight (66,7%) at the beginning of therapy, but after 6 monthstherapy most of subject of this research have normal BMI. Conclusion.There are some increasing of BMI from the beginning of the TB therapyuntil 6 months of TB therapy.Keywords: Tuberculosis, Body Mass Index, success of therapy.1. Program Studi Pendidikan Dokter, Fakultas Kedokteran UniversitasTanjungpura, Pontianak, Kalimantan Barat. 2. Pulmonology department of dr. soedarso General Hospital,Pontianak, Kalimantan Barat. 3. Nutrition department, Program Studi Pendidikan Dokter, FakultasKedokteran, Universitas Tanjngpura, Pontianak, Kalimantan Barat.